(untitled) (Progress Annals: Journal of Progressive Research, 2024)
As The primary goal of teaching reading is to help kids develop and reinforce their scientific understanding of accurate, fast, and creative reading this paper is about the issues of organizing reading lessons highliting the component issues of organizing.